Frente a las sendas del cognoscitivismo ético-judicial: algunas inquietudes y observaciones críticas a las propuestas de Luis E. Zamorano y Nelson J. Cuchumbé - Uribe Álvarez, Roberth (2023)
This article is a critical review of two papers written by professors Luis E. Zamorano and Nelson Cuchumbé, in which those authors vindicate models of ethical and judicial cognitivism. This critique purports to identify some problematic aspects associated with their cognitivist proposals, and also to ask some metaethical questions based on those problems.